The slave class of Sparta City State in the fifth century B.C (Raparin Journal of Humanities (RJH), 2024)
One of the most important social classes of Spartan city-state society was the slaves, known as the Helots. They were the majority of the other classes. As a result of Sparta's colonialist operations, most of its population was enslaved, especially both regions of  Laconian and Messenia, this class belonged to the state in terms of ownership, so they were used for many political and economic purposes and whatever heavy responsibilities were on their shoulders, on the other hand they were harshly supervised, because these were basically free people and forced As slaves, they therefore constantly tried to be free and regain their citizenship, until they carried out several rebellions and revolutions, known in human history as the Spartan Slave Revolution in the 5th century BC.This research, shed light on the characteristics of the slave class in the city-state of Sparta and the early stages of slavery in and their differences from other Social classes, then the way they were treated by the rulers of the city-state and revolted this class for their elementary rights, against the rulers of the city-state of Sparta.